Parallel and pipeline architectures for 2-D block processing - Azimi-Sadjadi, Mahmood R., author; Rostampour, A. R., author; IEEE, publisher (Colorado State University. Libraries, 1989)
This paper is concerned with the development and design of parallel and pipeline architectures for 2-D recursive and nonrecursive block digital filter. In this regard, several high speed structures using single-instruction multiple-data stream (SIMD) machines have been developed. These structures are designed based upon the specific nature of the block convolution processor, block recursive processor and block state-space processor both at the block and scalar levels.
Keywords: parallel architectures; two-dimensional digital filters